Civil Resistance Campaigns in Lithuania: How does the Ministry of National Defense Implement Advertising Campaign Strategies? - Uksaitė, Simona (Vilnius University Open Series, 2025)
The rapidly changing global security environment necessitates a reassessment of the concept of total defense, in which, the society plays a key role alongside the Lithuanian Armed Forces and allied forces in collective defense. Many modern threats to state security, such as information warfare, target the public’s will to resist. As a response, civil resistance has emerged as a critical tool to address these challenges. Its essential components include resilience, civic will, and knowledge with practical skills. Recognizing the growing importance of civil resistance, the Republic of Lithuania’s Strategy for Preparing Citizens for Civil Resistance was approved in September 2023. Coordinated by the Ministry of National Defense, this strategy aims to equip the public with the necessary information and tools to foster societal readiness. Lithuania’s historical examples of successful civil resistance serve as valuable references for shaping communication strategies to engage the public. In the field of security studies, civil resistance is a prominent research topic, analyzed as a vital element of the security policy. A key issue arises how the Ministry of National Defense, as the primary coordinator of civil resistance efforts, leverages the advertising campaign strategies to effectively implement the strategy’s goals and how it engages society in collective defense.